PENGEMBANGAN SISTEM INFORMASI PENERIMAAN SISWA BARU BERBASIS WEB DI SMP N 3 SAMIGALUH - Nurrokhim, Urfan; Elsera Astrianty, Ledy (Jurnal Simantec, 2024)
A web-based student admission information system is designed to address issues in the new student admission process at SMP N 3 Samigaluh, transforming the manual registration process into an integrated digital system. The research methods include data collection, needs analysis, system design, implementation, and system testing. The collected data is processed to determine the appropriate system requirements for a web-based admission system at SMP N 3 Samigaluh. The results of this research on the web-based student admission information system at SMP N 3 Samigaluh show that the system is designed to address various issues in the new student admission process. Through this system's development, the school can manage applicant data more effectively and conduct the selection process more transparently, which can enhance public trust in the school. The testing process in this research involves User Acceptance Testing (UAT) with prospective students and the SMP N 3 Samigaluh administration by running scenarios during the UAT. The testing results show that the web-based admission system is expected to bring significant benefits in terms of time efficiency, accuracy, and ease of information access, as well as improve the quality of the school's administrative services as a whole. Implementation results indicate a significant increase in operational efficiency, with automation features that reduce human error and improve data processing accuracy. This system successfully addresses information access and data management challenges, providing a comprehensive solution for the new student admission process.Keywords: Information System, New Student Admission, Website, SMP N 3 Samigaluh